2017
DOI: 10.3389/fevo.2017.00017
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Scale Genetic Structure of Wild Rice Zizania latifolia: The Roles of Rivers, Mountains and Fragmentation

Abstract: Wild rice (Zizania latifolia) is an important genetic resource and it has important ecological functions in aquatic ecosystems as well. Here, we used landscape genetics to investigate how the landscape features, including rivers, mountains and habitat fragmentation, affect the genetic connectivity or create dispersal barriers for Z. latifolia. In this report, seventeen populations from the Sanjiang Plain and its surrounding areas were genotyped by ten microsatellite markers. A high genetic differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
4
25
0
Order By: Relevance
“…A comparison of different models calculated by Migrate-n based on Bayesian factor values showed that model 2, with three population sizes and two migration rates (from Q. aliena to Q. dentata and from Q. dentata to Q. aliena ) was the best model for evaluating the historical gene flow (Chen et al, 2017 ) among the three oak species. This model verified the occurrence of bidirectional historical gene flow between Q. aliena and Q. dentata (Table 4 , Q. aliena → Q. dentata, M = 56.3; Q. dentata → Q. aliena, M = 57.0).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of different models calculated by Migrate-n based on Bayesian factor values showed that model 2, with three population sizes and two migration rates (from Q. aliena to Q. dentata and from Q. dentata to Q. aliena ) was the best model for evaluating the historical gene flow (Chen et al, 2017 ) among the three oak species. This model verified the occurrence of bidirectional historical gene flow between Q. aliena and Q. dentata (Table 4 , Q. aliena → Q. dentata, M = 56.3; Q. dentata → Q. aliena, M = 57.0).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, it is rarely cultivated as a crop and mainly survives untended in the wild. It should be noted that Z. latifolia is prevalent throughout China, except in Xinjiang and Tibet, and grows in lakes, ponds, rivers, marshes, and the wetlands [ 6 , 7 ]. It is particularly abundant in the middle and lower Yangtze River basin and Huai River basin [ 5 , 25 , 26 ].…”
Section: History and Present Situation Of The Z Latifolmentioning
confidence: 99%
“…The reasons for the low genetic diversity of the latter include restricted gene flow among populations, self-fertilization as a mode of reproduction, and genetic drift within populations [ 6 ]. Rivers, mountains, and habitat fragmentation influence the landscape-scale genetic structure of Z. latifolia [ 7 ]. Molecular evidence indicates that Zizania species likely originated in North America, thereafter spreading to East Asia and other parts of the world via the Bering Strait [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both rice and water oats are often planted next to each other as crops and given that water oats is larger than rice, < 10% land area would likely provide a 10% refuge by volume. In parts of China where water oats is not cultivated, the wild relative of water oats is often found in irrigation canals and ponds close to cultivated rice . Our results show that water oats growing near rice would likely provide suitable refuges for Bt resistance management of this serious rice pest, and structured refuges might be unnecessary.…”
Section: Discussionmentioning
confidence: 99%